Transmigration Archives as History Learning Media for History Education Study Programme Students of STKIP PGRI Bandar Lampung - Tama, Ozi Hendra; Kurniawan, Putut Wisnu; Suryati, Wawat; Nanda, Made (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This study aims to determine the benefits of the Transmigration Archive as a History Learning Media for History Education Study Programme Students of STKIP PGRI Bandar Lampung.  The research method used in this research is using a descriptive qualitative approach. Data collection techniques used in this research are literature study techniques, observation, interviews, and documentation. Data validity techniques use data source triangulation and for data analysis using data reduction, data presentation, and conclusion drawing. Transmigration archives are one of the sources that can be used as a medium for learning history, the transmigration archive was chosen because Lampung Province is the first transmigration site in Indonesia and there is also a transmigration museum that stores transmigration archives. There are various kinds of transmigration archives that can be found. currently there are various learning media used to support success in learning activities, one of which is by using transmigration archives. The results showed that the use of transmigration archives as learning media can be well received by students and can be used as one of the history learning media.